2021
DOI: 10.1155/2021/4729465
|View full text |Cite
|
Sign up to set email alerts
|

p53 Inhibition Protects against Neuronal Ischemia/Reperfusion Injury by the p53/PRAS40/mTOR Pathway

Abstract: The underlying mechanisms of cerebral ischemia/reperfusion (I/R) injury are unclear. Within this study, we aimed to explore whether p53 inhibition exerts protective effects via the p53/PRAS40/mTOR pathway after stroke and its potential mechanism. Both an in vitro oxygen-glucose deprivation (OGD) model with a primary neuronal culture and in vivo stroke models (dMCAO or MCAO) were used. We found that the infarction size, neuronal apoptosis, and autophagy were less severe in p53 KO mice and p53 KO neurons after c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…As is known, the mechanisms responsible for cerebral ischemia-reperfusion injury are relatively complex, and the related theories mainly include mitochondrial energy metabolism dysfunction, intracellular Ca 2+ Cheng et al, 2003). Besides, p53-de ciency or pharmacological suppression of p53 can lessen neuronal injury and promote functional recovery after cerebral ischemia (Leker et al, 2004;Zhao et al, 2021). So Caspase-3 and p53 are known as the executing molecules that exert an apoptotic function in various apoptotic pathways (Guzenko et al, 2023;Liu et al, 2019;Broughton et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As is known, the mechanisms responsible for cerebral ischemia-reperfusion injury are relatively complex, and the related theories mainly include mitochondrial energy metabolism dysfunction, intracellular Ca 2+ Cheng et al, 2003). Besides, p53-de ciency or pharmacological suppression of p53 can lessen neuronal injury and promote functional recovery after cerebral ischemia (Leker et al, 2004;Zhao et al, 2021). So Caspase-3 and p53 are known as the executing molecules that exert an apoptotic function in various apoptotic pathways (Guzenko et al, 2023;Liu et al, 2019;Broughton et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As is known, the mechanisms responsible for cerebral ischemia-reperfusion injury are relatively complex, and the related theories mainly include mitochondrial energy metabolism dysfunction, intracellular Ca 2+ Cheng et al, 2003). Besides, p53-de ciency or pharmacological suppression of p53 can lessen neuronal injury and promote functional recovery after cerebral ischemia (Leker et al, 2004;Zhao et al, 2021). So Caspase-3 and p53 are known as the executing molecules that exert an apoptotic function in various apoptotic pathways (Guzenko et al, 2023;Liu et al, 2019;Broughton et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The over-expression of pPRAS40 can reduce brain ischemia/reperfusion (I/R) damage and autophagy by activating mTOR. Not only that, studies have suggested that there is a negative feedback relationship between P53 and PRAS40, and P53 can be inhibited by its downstream factor PRAS40 (Havel et al, 2015;Zhao et al, 2021). In three groups of mice experiments: P53 KO mice (P53−/−), heterozygous (P53+/−) mice, and WT mice (P53+/+), the results showed that both P53 KO and heterozygous groups had an improved neurological function and reduced area of cerebral infarction, and P53 KO group showed a better protective effect (Havel et al, 2015).…”
Section: Figurementioning
confidence: 99%